PENGARUH SUSTAINABILITY REPORT DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Desi Fitria; Diva Sintia; Ahmad Sumarlan (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the effect of Sustainability Report and Good Corporate Governance (GCG) disclosure on financial performance in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Financial performance is proxied by Return on Assets (ROA), while Sustainability Report is measured based on the disclosure index and Good Corporate Governance is proxied through the audit committee. This study uses a quantitative method with secondary data in the form of financial reports and corporate sustainability reports. The sampling technique uses a purposive sampling method with a total sample of 17 SOEs over five years of observation, resulting in 85 observations. Data analysis was performed using multiple linear regression with the help of IBM SPSS 27 software. The results of the study indicate that partially Sustainability Report and Good Corporate Governance do not have a significant effect on financial performance. Simultaneously, the two independent variables also do not have a significant effect on the financial performance of SOEs. The coefficient of determination indicates that Sustainability Reports and Good Corporate Governance only explain 2.3% of financial performance, with the remainder influenced by variables outside the research model. This finding indicates that sustainability disclosure and corporate governance implementation have not been fully determinants in improving the financial performance of state-owned enterprises (SOEs) during the study period. Keywords: Sustainability Report, Good Corporate Governance, Financial Performance, ROA, SOEs